CLASSIFICATION OF POLYMER COMPOSITES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article discusses the advantages of polymer composite materials, classifies them, describes the properties and examples of the use of materials in various applications. Composites penetrate our everyday life, are used in construction, medicine, oil and gas industry, transport, sports, aerospace. Advantages of heterogeneous polymer compositions compared to homogeneous polymers. The modern era can be called the age of polymers and composite materials.